Study of Adoption of Improved Technologies in Black Gram Crop - Singh, Lokendra Kumar (Journal for Research in Applied Sciences and Biotechnology, 2024)
India is largest producer of pulses in world with 25 per cent share in global production. Chickpea, Pigeon Pea. MungBean, UradBean, lentil and Field Pea are important pulses crop contributing 39.00 per cent, 21.00 per cent, 11.00 per cent, 7.00 per cent and 5.00 per cent to the total production of pulses in the country. The total production was estimated 14.56 million tones and an area of 23.63 million hectares with average productivity 625kg/ha. (www agro pedia. Nic in.2015) Over 75% of the total of Black gram is generally known as dal milling or, dehulling. Milling means removal of the outer husk and splitting the grain into two equal halves. Dalmilling is one of the major food processing industries in the country, next only to rice milling. Black gram used as daal and as ingredient in snacks like idly, dosa, vada and papad etc. Adoption of Improved practice is the more essential part of increasing the production, because the population is increase day to day and holding size is decrease, so dal price is highly explosion The first week of October 2015 noted of cost of Black Gram dal 150- 180 Rupees per kg in the retails just before one year the cost October 2014 was 75-85 Rupees per kg (sources individual market survey 2015 ). We need the more production of pulses, we solve this problems by the applied more technologies in their field.